Pneumocystis carinii (Delano? and Delano?, 1912) infections in some bird species - Özer, Edip; Şaki, Cem Ecmel; Sevgili, Murat; Aksin, Nursel; Aktaş, Münir (Scientific and Technical Research Council of Turkey, 1996)
The study was performed on the tissue samples taken from the lung, the liver and the spleen. A total of 154 chickens, 21 turkeys, 44 quails and 18 partridges were used in the investigation. After smear preparations, tissue samples were stanied with toluidine blue O and examined under the microscope for the presence of P. carinii. The results of microscopic examination indicated that 91 out 154 chicken samples (59.1%), 12 out of 21 turkey samples (57.1%). 10 out of 44 quail samples (22.7%) and 3 out of 18 partridge samples (16.7%)had P. carinii parasites. Parasites were encountered in the lungs more frequently than in the liver and the spleen. The parasite load was also higher in the lung than those in other organs. No morphological differences between parasites in various organs were observed. This study, for the first time in Turkey, reports the presence of P. carinii in poultry species.
Bazi Kanatlilarda Pneumocystis carinii (Delano? and Delano?, 1912) Enfeksiyonu
Keywords: Chicken; Partridge; Pneumocystis carinii; Quail; Turkey